MECHANISM OF LANTANUM METAL TRANSPORT IN MEMBRAN LIQUID WITH CARRIER SENYA WA MACROSIKLIS - Suyanta, Suyanta (Jurnal Penelitian Saintek, 2015)
The transport mechanism of lanthanum element in the supported liquidmembrane with macrocycle compound Di benzo IB crowns 6 carriers was studied. These transport are two kinds. that is chemical transport and potential transport. The chemical transport is done with two cell compartment (feed compartment and stripping compartment). and separate with membrane that prepare with DiBenzoIBCrown6. Poly Vinyl Chloride. Di Octyl Ptalate, Sodium tetra butyl borate in Tetra hydro furan solution. A 150 mL solution of La3+ JO-3 Min feed cell stirrer with300 rpm speed along 3 hour. The stripping phase is solution that varied the pH from 1 to B. The same way. then solution in the feed cell is varied from 10-1 M to 5.10-4 M. The potential transport is measured with the relative same cell. The potential transport measure with two kind reference electrode. Ag/AgCI reference electrode in the inner cell and calomel reference electrode in the outer cell. Inner cell is contain mixture solution KCL 10-3 M and La3+ IO-3 M and outer cell is contain solution La3" that variedfrom 10-8 to JO-J M. The chemical transport is effective at low pH (below pH 4) and high pH (upper pH 6). It is good way for separation of La3'. The transport ion La3+ is low at pH 4 - 6. It is good areafor applied as sensor membrane electrode that has minimal diffusion potential. The system has good correlation in potential membrane that gives slope value 19.36 as Nernst coefficient.